2007
DOI: 10.1038/ng1994
|View full text |Cite
|
Sign up to set email alerts
|

The Shwachman-Bodian-Diamond syndrome protein mediates translational activation of ribosomes in yeast

Abstract: The autosomal recessive disorder Shwachman-Diamond syndrome, characterized by bone marrow failure and leukemia predisposition, is caused by deficiency of the highly conserved Shwachman-Bodian-Diamond syndrome (SBDS) protein. Here, we identify the function of the yeast SBDS ortholog Sdo1, showing that it is critical for the release and recycling of the nucleolar shuttling factor Tif6 from pre-60S ribosomes, a key step in 60S maturation and translational activation of ribosomes. Using genome-wide synthetic genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
385
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(406 citation statements)
references
References 50 publications
19
385
2
Order By: Relevance
“…According to the previous studies, c-Myc is an important factor both in the ribosome biogenesis and the p53 stabilization (Menne et al, 2007;Dai and Lu, 2008). Our data also suggest that c-Myc affects the stabilization of p53 through rpL11-mediated HDM2 inhibition, but not p14 ARF .…”
Section: Discussionsupporting
confidence: 79%
“…According to the previous studies, c-Myc is an important factor both in the ribosome biogenesis and the p53 stabilization (Menne et al, 2007;Dai and Lu, 2008). Our data also suggest that c-Myc affects the stabilization of p53 through rpL11-mediated HDM2 inhibition, but not p14 ARF .…”
Section: Discussionsupporting
confidence: 79%
“…Work in yeast (Menne et al, 2007), mouse liver (Finch et al, 2011), Dictyostelium and SDS patient lymphoblasts (Wong et al, 2011) has suggested a role for Sbds in late ribosome assembly, with loss of Sbds function resulting in a subunit joining defect. To identify whether our Sbds ATG MO-injected embryos exhibited similar ribosome assembly defects, we generated ribosome profiles at 48 hpf under native polysome assembly conditions.…”
Section: Knockdown Of Zebrafish Sbds Recapitulates the Developmental mentioning
confidence: 99%
“…SBDS is a highly conserved, essential gene that functions in late maturation of the large 60S ribosomal subunit. Studies in a variety of organisms and SDS patient lymphoblasts suggest that mutations in SBDS result in ribosomal subunit joining defects associated with altered subunit ratios (Zhang et al, 2006;Menne et al, 2007;Finch et al, 2011;Wong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although structural features of the SBDS protein family suggested early on that these proteins may function in some aspect of RNA metabolism, the exact molecular function of the protein in mammalian cells has been difficult to determine. The Saccharomyces cerevisiae ortholog of SBDS, Sdo1, functions in ribosome biogenesis (Menne et al 2007;Moore et al 2010). However, SBDS in mammalian cells has been implicated in multiple pathways, including ribosome biogenesis (Austin et al 2005), cell motility (Wessels et al 2006;Leung et al 2010), reactive oxygen species regulation (Ambekar et al 2010), and stabilizing the mitotic spindle (Austin et al 2008).…”
mentioning
confidence: 99%
“…The eIF6 protein binds to an intersubunit bridge (Gartmann et al 2010) and must be removed before the subunit can join a small subunit to initiate translation. The release of Tif6 in yeast requires Sdo1 (Menne et al 2007) and the GTPase Efl1 (Senger et al 2001), a homolog of the translation translocation factor EF-G. Finch et al (2011) now provide compelling data that, like Sdo1, SBDS promotes the release of eIF6 from 60S subunits. Moreover, their data reveal that SBDS promotes the release of eIF6 by stimulating the GTPase activity of Efl1.…”
mentioning
confidence: 99%